Deteksi Gen sHBsAg sebagai Penanda Koinfeksi Hepatitis B pada Pengidap HIV di Kota Bandung - Naully, Patricia Gita; Romlah, Sitti (Politeknik Kesehatan Tanjung Karang, 2019)
Bandung is the city with the highest number of Human Immunodeficiency Virus (HIV) sufferers in West Java. HIV patients often have co-infection with Hepatitis B Virus (HBV). This condition can increase the risk of cirrhosis, liver cancer, and death. Co-infection status can be detected by the presence of the sHBsAg gene amplified using the nested Polymerase Chain Reaction (nested PCR) method. The aim of this study was to decide the number of HBV co-infection cases with the sHBsAg gene as a marker and factor influencing the presence of the gene in HIV patients in Bandung. This research used 50 human samples domiciled in Bandung which have been infected with HIV and never had a hepatitis test. Taking blood specimens was done on the people who had signed the informed consent. The detection of the sHBsAg gene started with genomic DNA isolation. Moreover, the purity and concentration of DNA isolation results were measured by the Nanodrop. The amplification process of the sHBsAg gene was done twice using two pairs of the specific primary. The amplification results were visualized by agarose electrophoresis method. Then, the data collected was analyzed by a logistic regression method. The laboratory results showed that 18 people (36%) had HIV-HBV co-infection, marked by the presence of the sHBsAg gene in their blood. Unsafe sexual activity, syringe drug use, and a vaccination profile were factors that significantly influence (p<0.05) on this co-infection.